The Real Effects of Financing and Trading Frictions - Zucchi, Francesca (Journal of Financial and Quantitative Analysis, 2024)
I develop a model revealing the interplay between a stock’s liquidity and the policies and value of the issuing firm. The model shows that bid-ask spreads increase not only the firm’s cost of capital but also the opportunity cost of cash, then lowering cash reserves, increasing liquidation risk, and reducing firm value. These outcomes are stronger when internalized by liquidity providers, simultaneously leading to a wider bid-ask spread. A two-way relation between the firm and the liquidity of its stock arises, implying that shocks arising within the firm or in the stock market have more complex implications than previously understood.